Identification of Worm Eggs in Faeces of Egrets (Egretta sp.) in Surabaya - Akbar Haryo Widhi Trismiharto; Suzanita Utama; Koesnoto Supranianondo; Djoko Poetranto; Setiawan Koesdarto (Universitas Airlangga, 2018)
The aim of this research was to identify worm eggs species that infected Egrets in Surabaya. A total of 40 samples were taken and faecal examination was conducted in the Laboratory by means of native, sedimentation, and floating methods, In floating method saturated brown sugar solution was used as floating media because brown sugar solution was faster in floating worm eggs. Then further examination of the worm eggs species were matched by microscopic taxonomy and textbook comparison observation. Eggs of three classes of helmints, Trematode, Cestode, and Nematode were found in faeces of Egrets in Surabaya. Species of the Nematode eggs found were Ascaris sp., Ascaridia galli, , Capillaria sp., Toxocara cati. Species of Cestode class egg found were Raillietina sp, from Trematode class were Echinostoma revolutum.